Understanding media literacy in relation to adolescent soft drink consumption behaviour - Mohd Shahid, Nur Nadirah; Ghazali, Hazrina; Abu Bakar, Ainul Zakiah; Othman, Mohhidin (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
This paper examines relationship between media literacy and the Theory of Planned Behavior (TPB) variables focusing on consumption of soft drink among adolescents in Klang Valley, Malaysia. In addition, this paper also determines soft drink consumption, level of media literacy and the influences of the TPB variables on the intention of soft drink consumption. A cluster sampling method was used in collecting data within the Klang Valley area. The sample consisted of 436 adolescents from secondary school, aged between 13 to 18 years old. Two main scales utilized were Media Literacy (ML) scale and TPB scale. The descriptive, multiple linear regression and Pearson product-moment correlation analyses were carried out to answer the research objectives. Results revealed that 36% of respondents drank a minimum of 1 can, bottle or glass of soft drink for the past seven days and possess good level of media literacy (35%). Meanwhile, 14% of variance in adolescents’ intention of soft drink consumption is explained by TPB variables. Additionally, the total media literacy score towards soft drink advertisement was significantly positively correlated with attitude (r = 0.250, p<.05) and subjective norms (r = 0.174, p<.05). Conversely, total media literacy was significant negatively correlated with intention to consume soft drink (r = -0.19, p<.05) and indicated that media literacy could lower the intention to consume soft drink, thus can reduce soft drink consumption among adolescents. The importance of this study is to help the authorities, soft drink marketers and producers in Malaysia to better understand media literacy and adolescent soft drink consumption behavior.